Cephalopod‐Derived Biopolymers for Ionic and Protonic Transistors. Issue 19 (14th April 2018) - Kautz, Rylan; Ordinario, David D.; Tyagi, Vivek; Patel, Priyam; Nguyen, Tam N.; Gorodetsky, Alon A.
Abstract: Cephalopods (e.g., squid, octopuses, and cuttlefish) have long fascinated scientists and the general public alike due to their complex behavioral characteristics and remarkable camouflage abilities. As such, these animals are explored as model systems in neuroscience and represent a well‐known commercial resource. Herein, selected literature examples related to the electrical properties of cephalopod‐derived biopolymers (eumelanins, chitosans, and reflectins) and to the use of these materials in voltage‐gated devices (i.e., transistors) are highlighted. Moreover, some potential future directions and challenges in this area are described, with the aim of inspiring additional research effort on ionic and protonic transistors from cephalopod‐derived biopolymers. Abstract : Cephalopods (e.g., squid, octopuses, and cuttlefish) are valuable sources of materials for both commercial and scientific purposes. The electrical properties of cephalopod‐derived biopolymers (eumelanins, chitosans, and reflectins) are highlighted and their applications in voltage‐gated ionic and protonic devices are described.